2007
DOI: 10.1210/en.2007-1083
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: The Neuroendocrinology of the Suprachiasmatic Nucleus as a Conductor of Body Time in Mammals

Abstract: Circadian rhythms in physiology and behavior are regulated by a master clock resident in the suprachiasmatic nucleus (SCN) of the hypothalamus, and dysfunctions in the circadian system can lead to serious health effects. This paper reviews the organization of the SCN as the brain clock, how it regulates gonadal hormone secretion, and how androgens modulate aspects of circadian behavior known to be regulated by the SCN. We show that androgen receptors are restricted to a core SCN region that receives photic inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 120 publications
4
57
0
2
Order By: Relevance
“…Collectively, the current and previous studies suggest that gonadal steroids enhance the diurnal variation in cardiovascular regulation. This conclusion is consistent with the welldocumented requirement of estrogen for the precisely timed surge of luteinizing hormone during the afternoon of proestrus, as well as for diurnal changes in locomotor activity (11,26). For these latter effects, current evidence implicates an interaction of estrogen with the biological clock emanating from the superchiasmatic nucleus (11,26); therefore, we speculate that the effects of OVX observed in the present study may use similar neuronal circuitry.…”
Section: Discussionsupporting
confidence: 92%
“…Collectively, the current and previous studies suggest that gonadal steroids enhance the diurnal variation in cardiovascular regulation. This conclusion is consistent with the welldocumented requirement of estrogen for the precisely timed surge of luteinizing hormone during the afternoon of proestrus, as well as for diurnal changes in locomotor activity (11,26). For these latter effects, current evidence implicates an interaction of estrogen with the biological clock emanating from the superchiasmatic nucleus (11,26); therefore, we speculate that the effects of OVX observed in the present study may use similar neuronal circuitry.…”
Section: Discussionsupporting
confidence: 92%
“…A functional master clock located in the suprachiasmatic nuclei (SCN) of the hypothalamus is necessary for rhythmic steroid synthesis and excretion (13,14). It has been hypothesized that exposure to light at wrong times, such as experienced during night shift work, can disrupt normal melatonin synthesis which in turn may increase estrogen production (11).…”
Section: Introductionmentioning
confidence: 99%
“…To add to this complexity, physiological rhythms, including endocrine function, are well documented (12,13). It has been shown that some of these endocrine signals can feedback to modulate circadian behavior and the SCN (14), whereas others, such as the glucocorticoids, modulate peripheral oscillators and have little effect on the SCN (15). Thus, the ubiquity of clock genes, clock-controlled molecules, and circadian rhythms in physiological signals places the circadian clock at the center of a complex web of regulation that if perturbed could have effects in disparate brain and body systems.…”
mentioning
confidence: 99%